Keris Mas' Jungle of Hope: A Sociological Reading - Noor, Rohimmi (2002)
The intention of this research is to analyse Keris Mas' Jungle of Hope from a sociological perspective. Keris Mas, Malaysia's first national laureate, wrote Rimba Harapan (Jungle of Hope) in 1998. In 1990, the novel was translated into English by Adibah Amin. The themes in the novel identified for analysis are conflict between the old and the new ways of life, Adapting to change, Fear of being displaced, Faith in God and Exploitation of human beings. These themes are analysed based on the three major sociological theories, namely, Functionalism, Marxism and Symbolic Interactionism that are believed as able to provide a sociological perspective to the analysis of the themes selected. While functionalism are able to provide a better understanding of the themes of conflict between the old and the new ways of life and Faith in God, Symbolic interactionism can be seen as being able to provide an insight into the theme of Adapting to change. Marxism, on the other hand, provides a better understanding of the themes related to Fear of being displaced and exploitation of human beings.